Isolated ACL Reconstruction Versus Combined ACL and Anterolateral Ligament Reconstruction: A Matched Case Series with Mean Follow Up of 9 Years. Issue 7 (30th July 2021) - Haidar, Ibrahim; FRADIN, Thomas; Rayes, Johnny; Vieira, Thais; Cédric, Ngbilo; Sonnery-Cottet, Bertrand; Saithna, Adnan
Objectives: The aim of this study was to report long term comparative clinical outcomes of isolated Anterior Cruciate Ligament (ACL) reconstruction versus combined ACL and Anterolateral Ligament (ALL) reconstruction in a matched pair analysis. Methods: A retrospective analysis of prospectively collected data was undertaken. Patients who underwent combined ACL and ALL reconstruction were matched 1:1 to patients who had undergone isolated ACL reconstruction using a propensity score. Matching was based upon age, BMI, side to side laxity difference, duration of time between injury and surgery, type of sports participation (e.g pivoting, contact), presence of concomitant meniscal injuries and their treatment. At the end of the study period all patients completed Lysholm, Tegner, IKDC and KOOS scores, and underwent telephone interview and medical notes review to determine whether they had experienced any complications or re-operations after the index procedure. Kaplan-Meier analysis was used to determine survivorship with respect to graft rupture rates in each group Results: 90 patients who underwent combined ACL and ALL reconstruction were matched to 90 patients who underwent isolated ACL reconstruction. The mean duration of follow up was 108.09±9.43 months (range 97-182). The combined ACLR and ALLR group had significant lower graft rupture rate (3.5%) than the isolated ACLR group (16%) (OR=5.306 ; CI =1.46-19.19 ; p=0.007) (Fig 1). There was no significant difference between groups with respect to non-graft rupture related reoperation rates (secondary meniscectomy, cyclops excision, arthroscopic lavage for infection or hemarthrosis). Contralateral ACL rupture rates were comparable between combined ACL and ALL reconstruction (16.27%) and isolated ACL reconstruction (19.5%) groups. The KOOS score was significantly higher in the combined group with respect to subdomains of pain (p=0.007) and quality of life (p=0.007). There was no significant difference in other KOOS domains, Tegner, Lysholm, or IKDC Conclusions: This study reports the first long-term results of combined ACL and ALL reconstruction. The results demonstrate a significantly lower graft failure rate when compared to isolated ACL reconstruction in a matched pair series with a minimum follow-up of 9 years. :